2003
DOI: 10.1023/b:phot.0000027514.56808.35
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Performance of Ginkgo biloba L. Grown Under High and Low Irradiance

Abstract: Diurnal variation in net photosynthetic rate (P N ) of three-year-old plants of Ginkgo biloba was studied under open, O (receiving full sunlight), net-shade, NS (40 % of photosynthetically active radiation, PAR), or greenhouse, G (25 % PAR) conditions. In all three conditions, P N was higher in morning along with stomatal conductance (g s ), and intercellular CO 2 concentration (C i ), while leaf temperature and vapour pressure deficit were low. The O-plants exhibited a typical decline in P N during midday, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
7
26
0
1
Order By: Relevance
“…This could be the reason that these plants are adapted to altitude ranging between 400-4 000 m where they can sustain strong fluctuations in irradiance (Ansari et al 1999, Singh 2000, Bahar 2002). The increase in C i with increasing irradiance suggested an increase in photorespiration rate at HA (Pandey et al 2003). HA plants have higher photorespiration rates, which is beneficial for plants to protect PS2 from high energy solar radiation (Streb et al 1998, Taub et al 2000.…”
Section: Discussionmentioning
confidence: 96%
“…This could be the reason that these plants are adapted to altitude ranging between 400-4 000 m where they can sustain strong fluctuations in irradiance (Ansari et al 1999, Singh 2000, Bahar 2002). The increase in C i with increasing irradiance suggested an increase in photorespiration rate at HA (Pandey et al 2003). HA plants have higher photorespiration rates, which is beneficial for plants to protect PS2 from high energy solar radiation (Streb et al 1998, Taub et al 2000.…”
Section: Discussionmentioning
confidence: 96%
“…The decrease of mesophyll thickness in R. emodi under low irradiance in respect to high irradiance is mainly due to the palisade parenchyma thickness decrease (Hanba et al 2002, Pandey and Nagar 2002, Pandey et al 2003. The increase in mesophyll, leaf, and epidermis thicknesses may explain the higher LMA in R. emodi in the field than in the greenhouse (cf.…”
Section: Discussionmentioning
confidence: 97%
“…It is believed that the stomatal index (SI) does not vary so much as SD, the first being so intrinsic to the species (Salisbury, 1927). However, we question the invariability of SI, since certain studies have shown the opposite (Lake et al, 2001;Liao et al, 2005;Miyazawa et al, 2006;Pandey et al, 2003;Zhao et al, 2006). In this study, we assessed the effect of environmental light on the leaf anatomy and plasticity of coffee plants, and enumerated the interference factors in leaf acclimation, specifically on stomata and epidermal structures.…”
Section: Introductionmentioning
confidence: 97%